2015
DOI: 10.6023/cjoc201409048
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances of KRN7000 Analogues and Their Immune Activities

Abstract: KRN7000 has widely biological activities, such as anti-tumor, anti-tuberculosis, anti-fungal, anti-virus, anti-inflammation, and against auto-immune diseases. As the potential immunomodulator, KRN7000 can effectively activate the natural killer T cells (NKT cells) and induce the secretion of IFN-γ and IL-4 cytokines. However, IFN-γ inhibited the activity of T helper 2 cells (T H 2) and IL-4 inhibited the activity of T helper 1 cells (T H 1), which mediated humoral as well as celluar immune reactions, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…8 Therefore, a number of subsequent studies have focused on the ability to control the cascade by attempting to bias the Th1/Th2 cytokine release profile by employing KRN7000 as the template. 4,9,10 So far, many clinical studies on the development of a novel CD1d-binding NKT cell ligand as an additive vaccine adjuvant based on KRN7000 analogues are ongoing (Th1 cytokine bias). 11 Besides, KRN7000 analogues bearing functional groups are potentially versatile in conjugation strategies through facile reactions with a wide range of substrates to form highly defined synthetic vaccines, which has prompted intense interest in the context of "self-adjuvanting" vaccines.…”
Section: Research Papermentioning
confidence: 99%
“…8 Therefore, a number of subsequent studies have focused on the ability to control the cascade by attempting to bias the Th1/Th2 cytokine release profile by employing KRN7000 as the template. 4,9,10 So far, many clinical studies on the development of a novel CD1d-binding NKT cell ligand as an additive vaccine adjuvant based on KRN7000 analogues are ongoing (Th1 cytokine bias). 11 Besides, KRN7000 analogues bearing functional groups are potentially versatile in conjugation strategies through facile reactions with a wide range of substrates to form highly defined synthetic vaccines, which has prompted intense interest in the context of "self-adjuvanting" vaccines.…”
Section: Research Papermentioning
confidence: 99%
“…[3,4] A large number of KRN7000 analogues and related compounds have been synthesized and their activity towards NKT cell-activation has been tested. [3][4][5][6][7][8][9][10] Modifications of KRN7000 are roughly based on three modifiable parts: sugar head moiety, ceramide part, and sugar-ceramide linkage. Sugar moiety modification studies suggested that: (1) α-glycosidic bond is essential for NKT cell-stimulation activity; (2) minor changes on sugar head can result in activity loss except that C-6 position can tolerate small substitutions.…”
Section: Introductionmentioning
confidence: 99%